2006
DOI: 10.1002/masy.200690017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biodegradable Nanocomposites Based on aPLA/PCL Blends for Food Packaging Applications

Abstract: Biodegradable blends of amorphous poly(lactic acid) (aPLA) and polycaprolactone (PCL) and nanocomposites of these blends were developed by melt blending. A morphological study of the bioblends was carried out by means of WAXS and SEM showing immiscible behavior. The nanocomposites were also characterized morphologically by WAXS, TEM and SEM, revealing high degree of interaction of the nanoclays with the aPLA. Mechanical, thermal and gas barrier properties of the different blends and nanocomposites were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
140
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(144 citation statements)
references
References 9 publications
2
140
0
2
Order By: Relevance
“…Table 10): i) use of coating with materials which would add hydrophobicity to the packaging material, ii) lamination of two or more biopolymers (co-extrusion), iii) use of an edible coating with the required barrier properties for the food and subsequently use biopolymers as primary packaging, iv) development of blends of biopolymers with different properties, some examples include PLA/PEG blends, PLA/PHA blends and PLA/PCL blends, v) chemical and/or physical modification of biopolymers, and vi) development of micro-and nanocomposites based on biopolymers [170,312]. Co-extruded laminated films are already widely used in food packaging applications.…”
Section: Non-medical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10): i) use of coating with materials which would add hydrophobicity to the packaging material, ii) lamination of two or more biopolymers (co-extrusion), iii) use of an edible coating with the required barrier properties for the food and subsequently use biopolymers as primary packaging, iv) development of blends of biopolymers with different properties, some examples include PLA/PEG blends, PLA/PHA blends and PLA/PCL blends, v) chemical and/or physical modification of biopolymers, and vi) development of micro-and nanocomposites based on biopolymers [170,312]. Co-extruded laminated films are already widely used in food packaging applications.…”
Section: Non-medical Applicationmentioning
confidence: 99%
“…Another typical investigative approach is the use of nanometric additives [315], which have been reported to dramatically change rheological properties of polymer melts and to improve functional properties such as barrier to gases and vapors, mechanical properties and thermal stability, for example, nanocomposites of the aPLA and aPLA/ PCL blends were obtained by melt-mixing with a properly modified kaolinite showed an improvement in these properties with regard to the polymers and blends without clay [312]. It was found that PLA based nanocomposites have exhibited higher rates of PLA biodegradation in compost by the addition of nanoclays, which was attributed to the high relative hydrophilicity of the clays, allowing an easier permeability of water into the polymer matrix and activating the hydrolytic degradation process [316].…”
Section: Non-medical Applicationmentioning
confidence: 99%
“…A reasonable way to solve the problems associated with the plastics waste, high crude oil prices and a gradual exhaustion of fossil resources seems to be the use of polymers derived from renewable resources. Currently the most popular bio-based polymer is poly (lactic acid) (PLA) synthesized from L-and D-lactic acid [5]. PLA can be also manufactured by the ring-opening polymerization of lactide [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, our efforts are centered on the comparative development of inorganic-organic hybrid nanocomposites with two different commercial clays: a kaolinite-based organoclay and a montmorillonite-based organoclay. Although there are some reported studies about the effect of kaolinite in other polymers such as nylon 6, polyethylene oxide, poly(vinyl pyrrolidone), polyhydroxybutyrate, ethylene-vinyl-alcohol, poly(lactic acid), and polyethylene glycol, [20][21][22][23][24][25] the influence in polyolefinic matrices is still not reported. Kaolinite (Al 2 Si 2 O 5 (OH) 4 ) is a 1 : 1 phyllosilicate containing a gibbsite octahedral layer and a silicon oxide tetrahedral sheet.…”
Section: Introductionmentioning
confidence: 99%